ANALISIS STRATEGI KEUNGGULAN BERSAING DALAM RANGKA MEMENANGKAN PERSAINGAN BISNIS PERBANKAN (studi pada Bank Nagari cabang utama Kota Pekanbaru) - Sri Utari Herman; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conducted at the main branch of Bank Nagari Pekanbaru .which is located in the street Jenderal Sudirman No. 337 Pekanbaru . This research aims to analyze competitive advantage strategy which is used by the Bank Nagari in effort to face and win the competition in banking business .The data collection method that author use in this study is interview, then author process data obtained by using descriptive analysis. The subject of the study are all employees who work on the division of finance and services totaling 6 people. And to strengthen research and interviews , the author also interviewed some of the customers .The results shows that the competitive advantage strategy used by the Bank Nagari is to create service differentiation drawn from five attributes such as : reliability , responsiveness , assurance , consulting services and physical evidence.Keyword : competitive advantage strategy, differentiation, and service differentiation.